Bronchiectasis in an Iranian patient with Rothmund–Thomson syndrome: a case report and review of the literature - Seyed Ahmad Tabatabaii; Saba Ramezani; Sharareh Kamfar; Nazanin Farahbakhsh (Journal of Medical Case Reports, 2026)
Abstract Background Rothmund–Thomson syndrome (RTS) is a rare autosomal recessive disorder with approximately 400 reported cases worldwide. While the syndrome typically presents with characteristic features, such as poikiloderma and skeletal abnormalities, respiratory manifestations are uncommonly reported, making this case a unique addition to the scientific literature. Case presentation A 14-year-old Iranian female presented to our center with persistent respiratory distress refractory to various treatments. Clinical examination revealed characteristic features of RTS including sparse hair, eyebrows, and eyelashes, along with generalized poikiloderma and telangiectasias. Imaging studies demonstrated multiple bronchiectases in the lungs. The patient was diagnosed with RTS through comprehensive clinical evaluation and genetic testing. Despite extensive investigations, including immunological workup and screening for common causes of bronchiectasis, no alternative etiology was identified. Conclusions This case represents one of the few documented instances of bronchiectasis in RTS and the first reported case in an Iranian patient, highlighting the importance of considering respiratory complications in the clinical spectrum of RTS. Early recognition and appropriate management of such complications may significantly impact patient outcomes.